Summer Lightning : A Guide to the Second Battle of Manassas - Spruill, Matt (Book collections on Project MUSE., 2013)
From August 28 to August 30, 1862, Union and Confederate armies fought for the second time on the Manassas, Virginia, battlefield. The Battle of Second Manassas, or Second Bull Run, was the culmination of General Robert E. Lee's campaign after the Seven Days to shift the fighting from the vicinity of Richmond to northern Virginia. Lee's victory placed him in a position to carry the war north of the Potomac River and set the stage for the Maryland Campaign of 1862. Summer Lightning is a battlefield guide that sequentially follows the fighting from Brawner's Farm on August 28 to the final Confederate attacks against Union positions at Henry Hill on August 30. Summer Lightning uses a series of twenty "stops" with multiple positions to guide the reader through the battlefield and to positions and routes used by both armies, thus providing a "you are there" view of the engagement. With easy-to-follow directions, detailed tactical maps, extensive eyewitness accounts, and editorial analysis, the reader is transported to the center of the action. A detailed order of battle for both armies is provided, as well as information on important sites away from the main battlefield